Trends in the digitalization of the banking sector: an international aspect - Elena Kirillova; Teymur Zulfugarzade (Problems of Information Society, 2022)
The study analyzes the main features of the use of digital technologies in the financial and banking sector at the international level. In the paper, we can conclude: the customer's digital identifier is the main attribute when using technology platforms in the banking sector; the norms on personal data protection and information security requirements should apply to the customer's digital identifier; since the digital identifier is analogous to a passport, we can say that the digital identifier can contain more information about an individual and allows to participate in digital civil turnover. The study proposes a method for assessing the degree of digitization of banks by the level of automation of key processes; by the number of online services provided; by the speed of transactions; by the availability of online services around the clock; by the range of digital technologies used; by the volume of online sales and the volume of transactions carried out using digital technologies.